PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA PT SALAD SEGAR LESTARI DI JAKARTA - Ramadhan, Fajar; Prabowo, Budhi (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine how much influence leadership and work discipline have on employee performance at PT Salad Segar Lestari Jakarta either partially or simultaneously. The method used is descriptive quantitative. The sampling technique used saturated sampling where the entire population was used as a sample, in this study there were 65 respondents. The analysis used in this study uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results showed that there was a positive influence between leadership and employee performance partially. Where is the simple linear regression equation Y = 18,557 + 0.571 X1 means that it has a positive effect, the correlation test r = 0.593 is included in the strong category, the coefficient of determination is 34.1% and the remaining 65.9% is influenced by other factors, the t test is tcount 5.840 > ttable 1.669 then Ha1 is accepted and Ho1 is rejected. The results showed that there was a positive influence between work discipline and employee performance partially. Where is the simple linear regression equation Y = 14,655 + 0.672 X2 means that it has a positive effect, the correlation test r = 0.764 is included in the strong category, the coefficient of determination is 57.7% and the remaining 42.3% is influenced by other factors, the t test is tcount 9.401 > ttable 1.669 then Ha2 is accepted and Ho2 is rejected. The results showed that there was a positive influence between leadership and work discipline variables on employee performance simultaneously, where the multiple regression equation Y = 14,410 + 0.018 X1 + 0.659 X2 means that it has a positive effect, the multiple correlation test r = 0.764 is included in the strong category, the coefficient of determination is 57.1% and the remaining 42.9% which is influenced by other factors, the f test of fcount 43.511 > ftable 2.75 means that it can be concluded that the variables of leadership and work discipline have a significant effect on employee performance